2003
DOI: 10.1289/ehp.5478
|View full text |Cite
|
Sign up to set email alerts
|

Production of proinflammatory mediators by indoor air bacteria and fungal spores in mouse and human cell lines.

Abstract: We compared the inflammatory and cytotoxic responses caused by household mold and bacteria in human and mouse cell lines. We studied the fungi Aspergillus versicolor, Penicillium spinulosum, and Stachybotrys chartarum and the bacteria Bacillus cereus, Pseudomonas fluorescens, and Streptomyces californicus for their cytotoxicity and ability to stimulate the production of inflammatory mediators in mouse RAW264.7 and human 28SC macrophage cell lines and in the human A549 lung epithelial cell line in 24-hr exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 40 publications
5
89
0
4
Order By: Relevance
“…are strongly associated with moisture damage. Streptomyces have, furthermore, been found to stimulate the production of pro-inflammatory mediators even more strongly than many problem fungi 43 , and this is of potential relevance in the development of immunological disorders.…”
Section: Bacterial Composition Of Filter Dustmentioning
confidence: 99%
“…are strongly associated with moisture damage. Streptomyces have, furthermore, been found to stimulate the production of pro-inflammatory mediators even more strongly than many problem fungi 43 , and this is of potential relevance in the development of immunological disorders.…”
Section: Bacterial Composition Of Filter Dustmentioning
confidence: 99%
“…fluorescens (N78), and Str. californicus (A4) were all isolated and identified in previous studies (Huttunen et al , 2003. The fungal strains were cultured on 2% malt extract agar and bacterial strains on tryptone yeast glucose agar as a dense culture and incubated in the dark at 25°C for 7 days and 20°C for 5 days, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier studies comparing the effects of fungal and bacterial exposure in vitro indicated that the importance of exposure to bacteria, especially gram-positive actinomycetes, might have been underestimated (Huttunen et al 2003). Because the numbers of bacteria in indoor air are frequently higher than the number of fungi, exposures to bacteria and their interactions with fungi are of great importance (Flannigan et al 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Otras propiedades importantes de los hongos están relacionadas con sus potencialidades patogénicas, es decir, la capacidad que tienen muchas especies para provocar enfermedades al hombre que está en contacto con ellos (Huttunen et al, 2003;Anderson, 2003;Denning, 2006;Nevalainen y Morawska, 2009;Haleem y Mohan, 2012). En varias investigaciones realizadas en archivos y bibliotecas, se ha demostrado que estos agentes son la causa de muchas enfermedades profesionales y patologías situacionales (Florian, 2003;Valentín, 2010;Haleem y Mohan, 2012).…”
Section: Introductionunclassified